Strategic Accounting for Innovation: Empowering Entrepreneurship in the Modern Era - Sharon, St Salmah; Firman, Afrizal; Monalisa, Monalisa; Muchtar, Muchtar; Paranoan, Natalia; Arif, Muh (Technium Social Sciences Journal, 2024)
This study explores how modern accounting practices drive entrepreneurial success. Through a comprehensive literature review, case study analysis of successful entrepreneurial firms, and interviews with companies that have implemented innovative accounting practices, this research uncovers the pivotal role of adaptive accounting in financial planning, risk management, and strategic decision-making. The findings highlight that companies utilizing advanced accounting tools are better equipped to handle the complexities of modern business, achieve greater financial transparency, and drive continuous innovation. The study also emphasizes the importance of accounting education and professional development in leveraging technology for these purposes. Additionally, the implications for policymakers and stakeholders underscore the necessity of a regulatory framework that supports advanced accounting practices. This study provides valuable insights for practitioners aiming to utilize modern accounting as a catalyst for business innovation and entrepreneurial success.